(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The economy of India had undergone significant policy shifts in the beginning of the 1990s. This new model of economic reforms is commonly known as the LPG or Liberalization, Privatization and Globalization model. The primary objective of this model was to make the economy of India the fastest developing economy in the globe with capabilities that help it match up with the biggest economies of the world.